2020
DOI: 10.1093/oso/9780198788348.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Scientific Computation

Abstract: This book explains how to use the bulk synchronous parallel (BSP) model to design and implement parallel algorithms in the areas of scientific computing and big data. Furthermore, it presents a hybrid BSP approach towards new hardware developments such as hierarchical architectures with both shared and distributed memory. The book provides a full treatment of core problems in scientific computing and big data, starting from a high-level problem description, via a sequential solution algorithm to a parallel sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In the same manner, we can compare a 3D domain of size s x × s x × s x /2 to the rotated parallelepiped, and find a factor of 43. We remark that the truncated octahedron that is used in Bisseling 31 for the 3D domain and has a factor of 1.68 cannot be used for our multilevel method, since truncated octahedra are not self‐similar.…”
Section: Skew Partitioning In 2d and 3dmentioning
confidence: 89%
See 1 more Smart Citation
“…In the same manner, we can compare a 3D domain of size s x × s x × s x /2 to the rotated parallelepiped, and find a factor of 43. We remark that the truncated octahedron that is used in Bisseling 31 for the 3D domain and has a factor of 1.68 cannot be used for our multilevel method, since truncated octahedra are not self‐similar.…”
Section: Skew Partitioning In 2d and 3dmentioning
confidence: 89%
“…Another advantage of using a skew domain partitioning is that the amount of communication that is required is reduced when compared to a square partitioning. In Bisseling, 31 it is estimated that for the Laplace problem, the communication is asymptotically reduced by a factor of 2 for the 2D diamond shape. If we instead compare the diamond shape to a rectangular domain with the same number of nodes (having the same number of nodes with a square domain is impossible), we find that communication is reduced by a factor of 32.…”
Section: Skew Partitioning In 2d and 3dmentioning
confidence: 99%
“…8 illustrates this. It has been shown that the communication volumes of subsequent splits in a general partitioning method for parallel SpMV are additive; a proof can be found in [5], [20]. For RB, this means that…”
Section: Recursive Bipartitioningmentioning
confidence: 99%